2019
DOI: 10.1021/acs.jpcb.8b10359
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mono- and Divalent Ions in Peptide Glu-Asp-Arg–DNA Interaction

Abstract: The interaction of the regulatory biologically active peptide Glu-Asp-Arg (EDR) with DNA is considered by spectral, NMR, viscosimetry, and molecular dynamics methods. It was shown that EDR can partly penetrate into the major groove of DNA and affect the base atoms, mainly the N7 and O6 of guanine. It was observed that Mg 2+ ions can promote DNA−EDR interaction due to their effective screening of the negatively charged phosphate groups of DNA. This action of Mg 2+ remains in salted solution as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It was established that EDR can interact with the large groove of dsDNA, forming bonds with the N7 and O6 atoms of guanine. Mg 2+ ions enhance the binding of EDR to dsDNA due to their ability to screen the negatively charged phosphate groups of the dsDNA [83]. A similar mechanism of binding to dsDNA was established for AEDL, a bronchoprotective peptide [41].…”
Section: Short Peptides + Dnamentioning
confidence: 72%
“…It was established that EDR can interact with the large groove of dsDNA, forming bonds with the N7 and O6 atoms of guanine. Mg 2+ ions enhance the binding of EDR to dsDNA due to their ability to screen the negatively charged phosphate groups of the dsDNA [83]. A similar mechanism of binding to dsDNA was established for AEDL, a bronchoprotective peptide [41].…”
Section: Short Peptides + Dnamentioning
confidence: 72%
“…Short peptides structurally and functionally remind zinc fingers, the DNA-binding domains of transcription factors. In particular, metal, iron, and zinc ions similarly affect the DNA binding parameters of a synthetic peptide containing the finger domain from the erythroid transcription factor GATA-1 [135], peptides (MBP-DF) [136], and the ultrashort peptide EDR [137].…”
Section: Interaction Of Short Peptides With Cis-regulatory Elements O...mentioning
confidence: 99%
“…Coordination of neutral peptides with metal ions may occur through the terminal amino group and/or the carbonyl oxygens of both the amide groups and the carboxylic terminus. These structures are frequently referred to as being charge-solvated (CS), and this type of binding is common in complexes involving alkali and alkaline earth metals. Alternatively, the amide groups of the peptide backbone may be present as iminols, which coordinate the metal ion via iminol nitrogens (described as Im-binding) with iminol OH groups assisting in delocalizing the charge in some structures by hydrogen bonding to other basic sites. , IRMPD (infrared multiple photon dissociation) studies have shown that Ni 2+ complexes with dipeptides and tripeptides prefer iminol binding. ,, …”
Section: Introductionmentioning
confidence: 99%